Lignin composite ionic liquid lubricants with excellent anti-corrosion, anti-oxidation, and tribological properties - Zhang, Chaoyang; Yang, Zhiquan; Huang, Qing; Wang, Xingwei; Yang, Wufang; Zhou, Chunyu; Yu, Bo; Yu, Qiangliang; Cai, Meirong; Zhou, Feng (Friction, 2023)
A new type of lubricating material (BTA-P 4444 -Lig) was synthesized by combining lignin with tetrabutylphosphorus and benzotriazole. The tribological properties, corrosion resistance, and anti-oxidation properties of BTA-P 4444 -Lig as a lubricant were investigated. The lubricating material exhibits excellent friction reduction and wear resistance, as well as good thermal stability and excellent oxidation resistance. Mechanistic analysis reveals that the active elements N and P in the lubricating material react with the metal substrate, and the reaction film effectively blocks direct contact between the friction pairs, affording excellent friction reduction and wear resistance. At the same time, the phenolic hydroxyl group in lignin reacts with oxygen free radicals to form a resonance-stable semi-quinone free radical, which interrupts the chain reaction and affords good anti-oxidant activity.